TINJAUAN YURIDIS TERHADAP ASET SITA UMUM PAILIT YANG DINYATAKAN SEBAGAI BARANG SITAAN NEGARA (STUDI PUTUSAN MAHKAMAH AGUNG NO. 156 K/PDT.SUS-PAILIT/2015) - RICKY FAUZAN (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. Mahmul Siregarf3. Muhammad Hamdan In running a buiness activity in baking field, board of directors frequently encounters a polemic that obliges them to make a decision and take responsibility for the bank which is potentially bankrupt. Board of derectors is the body of company which is authorized and fully responsible to manage the company for its sake, in line with its significance and objective, and represents the company inside and outside a court in accordance with the provisions in Article of Association. A systemic bank is the bank that, due to its size of asset, capital, and obligation as well as its involvement with other financial sector, can fail some parts or all parts of other banks or financial service, either operationally or financially, if it undergoes trouble or fails. The research problems are how standards are determined in a systemic bank, how a director's liability in a systemic bankis, and how fiduciary duty doctrine and business judment rule are implemented.